Generalized MIMO transmit preprocessing using pilot symbol assisted rateless codes - Bonello, Nicholas; Yang, Du; Chen, Sheng; Hanzo, Lajos (IEEE transactions on wireless communications, 2010)
In this paper, we propose a generalized multipleinput multiple-output (MIMO) transmit preprocessing system, where both the channel coding and the linear MIMO transmit precoding components exploit the knowledge of the channel. This was achieved by exploiting the inherently flexible nature of a specific family of rateless codes that are capable of modifying their code-rate as well as their degree distribution based on the channel state information (CSI), in an attempt to adapt to the time-varying nature of the channel. Moreover, we also propose a novel technique, hereby referred to as pilot symbol assisted rateless (PSAR) coding, where a predetermined fraction of binary pilot symbols is interspersed with the channel-coded bits at the channel coding stage, instead of multiplexing the pilots with the data symbols at the modulation stage, as in classic pilot symbol assisted modulation (PSAM). We will subsequently demonstrate that the PSAR code-aided transmit preprocessing scheme succeeds in gleaning more beneficial knowledge from the inserted pilots, because the pilot bits are not only useful for estimating the channel at the receiver, but they are also beneficial in terms of significantly reducing the computational complexity of the rateless channel decoder. Our results suggest that more than a 30% reduction in the decoder's computational complexity can be attained by the proposed system, when compared to a corresponding benchmarker scheme having the same pilot overhead but using the PSAM technique.